Práticas parentais maternas e a influência de variáveis familiares e do bebê - Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Nogueira, Sária Cristina [UNESP]; Altafim, Elisa Rachel Pisani (My University, 2013)
Parenting practices can be understood as the behaviors emitted by parents to educate and socialize their children. The present study investigates the influence of the parenting practices according to the baby sex and age, family configuration and number of children. For this, 50 adult mothers were questioned according to the Parental Styles Inventory for Mothers with Babies (IEPMB). An analysis with the results indicates that mothers with baby girls normally uses a more Positive Monitoring practice when compared with mothers with boy babies. A positive correlation (r = +0.54, p <0.001) was found, between the age of the baby and the practice of negligence, meaning that there is an increase of the usage in the practical as the baby age increases. Also a significant difference (p = 0.04) in the Inconsistent Punishment practice pointed out to the fact that mothers from nuclear families seem to use this practice more than mothers from other family configurations. And multiparous mothers use more Physical Abuse practical than primiparous mothers (p = 0.02). Concerning this analysis, we support a discussion in the present work about the importance of interventions that focus on the effect of specific positive practices, the reduction of negative practices and the role of the network support on the children development.

O presente artigo investigou a influência das variáveis idade e sexo do bebê, configuração familiar e número de filhos sobre as práticas parentais de mães de bebês. Participaram da pesquisa 50 mães adultas de bebês com até 22 meses de idade que responderam ao Inventário de Estilos Parentais para Mães de Bebês (IEPMB). Os resultados apontaram que mães de meninas utilizam mais a prática de Monitoria Positiva do que as de meninos (p=0,04) e, quanto mais velho o bebê mais utilizam a prática de Negligência (r= +0,54, p<0,001). Das características maternas observou-se que as mães de famílias nucleares utilizam mais a prática de Punição Inconsistente (p=0,04) do que as mães de outras configurações e mães multíparas utilizam mais a prática de Abuso Físico do que as mães primíparas (p=0,02). Discute-se a importância de intervenções pontuais que privilegiem práticas positivas resultando na diminuição das práticas negativas como apoio ao desenvolvimento infantil.
Maternal parenting practices and the influence of variables on the family and the baby
Keywords: Parental practice; Maternal behavior; Child development; Práticas educativas; Desenvolvimento infantil; Comportamento materno